Does Masked Hypertension Cause Early Left Ventricular Impairment in Youth? - Xiu-Xia Luo; Yongsheng Zhu; Yiqian Sun; Quanrong Ge; Jin Su; Hung-Kwan So; Man-Ching Yam; Fang Fang (Frontiers Media S.A., 2018)
Objectives: Masked hypertension (MH) is not uncommon in the youth and may increase risks of long-term cardiovascular impairment. However, little is known about the subclinical heart damage in this group of patients. Currently, 3-layer speckle tracking imaging based on two-dimensional echocardiography is feasible to detect the early signs of myocardial damage. We therefore aimed to investigate whether subtle changes of cardiac function occurred in the young MH patients by using advanced quantification with layer-specific speckle tracking.Methods: A total of 40 adolescents with MH (age 18 ± 3 years, 73% males) and 40 age-, gender-, race-, and height-matched normotensive volunteers were enrolled in our study. MH was defined as one or more of the ambulatory blood pressure (BP) parameters (24-h, daytime and night-time average BPs) higher than ≥ 95th percentile for gender and height according to the local reference. Both comprehensive two-dimensional echocardiography with layer-specific strain analysis and 24-h ambulatory BP monitoring were performed. Longitudinal strain and circumferential strain in endocardial, mid-myocardial, and epicardial layers were determined accordingly with the dedicated software (EchoPAC software version 201, GE Healthcare, Horten, Norway).Results: Compared with normotensive controls, youths with MH had higher ambulatory pulse rate and left ventricular mass index, and were more obese. Interestingly, similar ventricular volumes and ejection fraction were observed in the study groups, but further analysis with layer-specific strains revealed that endocardial and mid-myocardial longitudinal and circumferential mechanical function were decreased in the young MH subjects when compared to normotensive individuals (all p < 0.05). However, there were no difference regarding radial strain and apical rotation derived from traditional speckle tracking analysis.Conclusion: Subclinical change of LV mechanic function assessed by layer-specific speckle tracking is present in youth with MH despite considered as normal with conventional ways.Thus, MH in youth should be monitored closely instead of labeling as an entirely benign entity.